SOLUNUMSAL ASİDOZLU SIÇANLARDA BÖBREK KORTİKAL TOPLAYICI KANAL İNTERKALATE HÜCRELERDEKİ ULTRASTÜRÜKTÜREL DEĞİŞİKLİKLER - Seçkin, İsmail and URULUER, Bülent and Uzunalan, Mümin and Köktürk, Sibel and KURUŞ, Meltem and ŞATIROĞLU, Güngör (Cerrahpaşa Medical Journal, 2014)
Background and design.- Recent studies on cortical collecting tubules have supported that type- A intercalated cells have a H+-ATPase in apical membrane and a Cl- / HCO3- exchanger in basolateral membrane and thus secrete H+ and reabsorb HCO3-while type- B intercalated cells have a Cl- / HCO3- exchanger in apical membrane and a H+-ATPase in basolateral membrane and thus they secrete HCO3- and reabsorb H+. In our study we aimed to investigate the ultrastuructural changes in different intercalated cells in cortical collecting tubules of rat.s kidney with 12 and 24 hours respiratory acidosis. Results.- In the type A intercalated cells of rats with 12 and 24 hours respiratory acidosis, apical tubulo vesicles decreased in number while mitocondria, number and length of microvilli increased. In type B intercalated cells of 12 hours respiratory acidosis group there were no prominent ultrastuructural changes. However, in 24 hours respiratory acidosis group, we observed an increased traffic of vesicles to words the apical pole of type B intercalated cells. Mitochondrial density was also increased. Conclusion.- Our finding on the type A intercalated cells have supported the previous studies while the finding on type B intercalated cells were contraversial. As a conclusion we thought that type B intercalated cells showed morphological alterations reflecting changes in functional characteristic in response to chronic respiratory acidosis (24 hours), in addition to ultrastuructural changes in type A intercalated cells.